La educación para la ciudadanía: entre la objeción de conciencia y recursos contencioso-administrativos - González-varas Ibáñez, Alejandro (Anuario de Derechos Humanos. Nueva Época, 2009)
This article studies the legal debate about the introduction of the matter Citizenship Education in the Spanish educational legal system. The author analyzes which legal ways can be put into practice by persons that think this matter damages their rights. It pays attention to appeals of its regulation, and conscious objection.